Transparency in International Adjudication: A Critical Analysis through the Lens of the ICTY and Global Geopolitics (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This reflective article critically explores the concept of transparency in internationaladjudication, focusing on the International Criminal Tribunal for the former Yugoslavia (ICTY) andincidents of assassinations labeled as accidents. It examines the implications of transparency on thecredibility of international courts, drawing attention to the ICTY's impact on humanitarian law. Thenarrative delves into the maintenance of transparency, citing an illustrative case and its significance inunderstanding justice, peace, and international jurisprudence. The essay also addresses diplomaticdilemmas, contemplating the role of tribunals in global geopolitics and questioning the nature ofinternational friendships, particularly in the context of India and Russia. The discussion extends todouble standards in intelligence assessments, emphasizing the complexities of geopolitics and thequest for justice.The essay concludes by addressing double standards in intelligence assessments, highlighting thecomplexities of global geopolitics and the pursuit of justice.